2022
DOI: 10.3390/ani12202725
|View full text |Cite
|
Sign up to set email alerts
|

Serum Analytes of American Mink (Neovison Vison) Challenged with Aleutian Mink Disease Virus

Abstract: Black American mink (Neovison vison), which had been selected for tolerance to Aleutian mink disease virus (AMDV) for more than 20 years (TG100) or were from herds that have been free of AMDV (TG0), along with their progeny and crosses with 50% and 75% tolerance ancestry, were inoculated with a local isolate of AMDV. Blood samples were collected from 493 mink between 120 and 1211 days post-inoculation, and concentrations of 14 serum analytes were measured. Distributions of all analytes significantly deviated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…( 2022 ) in a nutritional study of male minks. These authors did not find differences between sex and other variables, such as time and degree of tolerance (Farid and Rupasinghe 2022 ), or the level of protein or metabolic energy in the diet (Han et al. 2022 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…( 2022 ) in a nutritional study of male minks. These authors did not find differences between sex and other variables, such as time and degree of tolerance (Farid and Rupasinghe 2022 ), or the level of protein or metabolic energy in the diet (Han et al. 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, Farid and Rupasinghe ( 2022 ) found that infection with Aleutian mink disease virus (AMDV) increased the levels of TP and γ-globulins in American mink, which could help in the diagnosis of diseases and the identification of tolerant minks. The TP concentrations in this study were similar to those reported by Farid and Rupasinghe ( 2022 ) and Han et al. ( 2022 ) in a nutritional study of male minks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation